Impact of Blockholder Ownership and Dividend Payout on Government-Linked Companies(GLCs) Value in Malaysia - Nor Razuana, Amram (2010)
Government-linked companies (GLCs) play important role in the development of Malaysian economy. Therefore, this paper examines the relationship between blockholder ownership and dividend payout towards the firm value among government linked companies (GLCs) in Malaysia. By assessing the relationship the second larges ownership data in GLCs is used to looked government intervention. This study is based on a sample of 30 firms over a period from 2004 to 2009. Statistical techniques of correlation and regression have been used to explore the relationship between blockholder ownership, dividend payout and firm's value. The finding indicates that there is significant impact between dividend payout and firm value.